Development of empirical equations between uniaxial compressive strength and point load index: a case study for sandy dolomite - Meiqian Wang; Wenlian Liu; Haiming Liu; Wei Xu (Scientific Reports)
Abstract In this research, the Yuxi section of Central Yunnan Water Diversion Project in Southwest of China, including the tunnel and the traversed sandy dolomite along its route, was selected as the research area, and different sandification degrees classification, including strongly sandy, medium sandy, and weakly sandy, were collected. A comprehensive suite of geotechnical tests was conducted, which included CT scanning, cathodoluminescence, density, porosity, softening coefficient, saturation coefficient, point load test, and uniaxial compressive strength (UCS) test. The Point load index (I s(50) ) model for predicting UCS of different sandification degrees dolomite under dry and saturated conditions were analyzed by least square regression, and the empirical equation with correlation coefficient (R 2) between 0.7372 and 0.8347 are obtained. To evaluate the performance of the prediction model, some statistical parameters, including MAE, MSE and RMSE, are calculated to evaluate the effectiveness of the empirical equation. The results of this study indicate that the point load test is one of the reliable methods for estimating the UCS of sandy dolomite under both dry and saturated conditions. Furthermore, the results of the point load test on sandy dolomite hold significant reference value for their practical application and promotion in the field, suggesting a broader utility in engineering practice.